2016
DOI: 10.1080/03007995.2016.1222516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Expanded Disability Status Scale and the Multiple Sclerosis Functional Composite as clinical endpoints in multiple sclerosis clinical trials: quantitative meta-analyses

Abstract: There is controversy about the sensitivity of the EDSS and MSFC in detecting the progression of MS disease. The EDSS and MSFC are effective tools to assess the clinical severity and progression of MS disease. MSFC is more sensitive than EDSS in detecting the progression of MS disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
0
11
0
3
Order By: Relevance
“…This comparative approach would be greatly facilitated by the increased use of existing symptom and disability assessment scales and the validation of new ones. The Expanded Disability Status Scale (4) is the most widely used neurological exam scale in clinical trial settings, but focuses primarily on mobility, while the Multiple Sclerosis Functional Composite (5) scale is considered more sensitive (6), however, both are time consuming. In contrast, the assessing relapse in multiple sclerosis (ARMS) questionnaire (7) is a less rigorous, but more practical method.…”
Section: Determining the Validity And Severity Of A Relapsementioning
confidence: 99%
“…This comparative approach would be greatly facilitated by the increased use of existing symptom and disability assessment scales and the validation of new ones. The Expanded Disability Status Scale (4) is the most widely used neurological exam scale in clinical trial settings, but focuses primarily on mobility, while the Multiple Sclerosis Functional Composite (5) scale is considered more sensitive (6), however, both are time consuming. In contrast, the assessing relapse in multiple sclerosis (ARMS) questionnaire (7) is a less rigorous, but more practical method.…”
Section: Determining the Validity And Severity Of A Relapsementioning
confidence: 99%
“…The standardized assessment tools currently used for ambulation are the gait component of the Expanded Disability Status Scale (EDSS) 1 and the Timed 25-Foot Walk (T25FW) test, a component of the Multiple Sclerosis Functional Composite. [2][3][4] Limita-tions have been reported with both the EDSS gait component and the T25FW test. [5][6][7][8] The gait component of the EDSS is an ordinal scale with criteria for ambulation limited to the distance walked and use of a unilateral or bilateral assistive device.…”
mentioning
confidence: 99%
“…However, the EMA does acknowledge that there is a need for alternative measures (see below for information on the Multiple Sclerosis Outcome Assessments Consortium [ 68 , 69 ]), and research in this area has been active for many years. The MSFC was first introduced almost 20 years ago to address some of the limitations of the EDSS [ 17 ], and a recent meta-analysis has shown it to be more sensitive than the EDSS for detecting progression of MS [ 70 ]. The MSFC was included in over half (9/16) of the phase III RRMS trials identified in the current evaluation, although it was a primary endpoint in only one [ 43 ].…”
Section: Discussionmentioning
confidence: 99%